2010
DOI: 10.1007/s00271-010-0239-z
|View full text |Cite
|
Sign up to set email alerts
|

Teaching irrigation science and water management: accepting professional diversity. Editorial

Abstract: Water matters in a world that will soon have to grow food for billions more people. In that context, how should we educate aspiring professionals in the field of irrigation and water resource management? Before attempting an answer to that question we need to explore how the practice and science of irrigation have changed in recent decades.First, we outline the history of irrigation development, identifying the important research issues that were characteristic for each period. The intent is to delineate major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…In this context, the multimedia teaching resource management evaluation model in the big data environment has gradually shown its value [7]. In view of the deficiencies in the studies of multimedia teaching resource construction method and resource management evaluation model at present, a multi-media teaching resource management evaluation model is first proposed in this paper based on the ontology and hypergraph theory [8][9][10]. Guided by the model, the construction method for the multimedia teaching resource management evaluation model is studied in the open big data environment.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the multimedia teaching resource management evaluation model in the big data environment has gradually shown its value [7]. In view of the deficiencies in the studies of multimedia teaching resource construction method and resource management evaluation model at present, a multi-media teaching resource management evaluation model is first proposed in this paper based on the ontology and hypergraph theory [8][9][10]. Guided by the model, the construction method for the multimedia teaching resource management evaluation model is studied in the open big data environment.…”
Section: Introductionmentioning
confidence: 99%
“…Water supply matters in the world that will soon have to grow food for billions more people as world population is projected to peak at 9.3 billion in 2050, an increase of 28%. Analysis showed that the total crop water requirement of all major crops increased with the rising temperature thereby increasing the simulated irrigation water demand (Kijne, 2010;Surendran et al, 2014). In the future, food and livelihood security may be challenged due to global environmental changes, particularly global climatic changes that evidence has *Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…Research over recent decades has contributed tremendously to the advancement of on-farm water and salt management (Oster and Wichelns, 2003;Hillel and Vlek, 2005;Kijne, 2006;Kijne, 2011). Means became available to utilize rainfall and groundwater within or just below the potential root zone, as a water source to supply in crop water requirements (Ayars et al, 2006;Jhorar et al, 2009;Isidoro and Grattan, 2011;Singh, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Salt tends to accumulate in poorly drained soils under irrigation if inadequate water and salt management practices are applied. Furthermore, overirrigation may deteriorate the quality of water resources, because of salt pollution resulting from excessive drainage and leaching (United States Salinity Laboratory Staff, 1954;Van Schilfgaarde, 1990;Letey, 1994;Rhoades, 1997;Hillel, 2000;Oster and Wichelns, 2003;Hillel and Vlek, 2005;Kijne, 2006;Le Roux et al, 2007;Van Rensburg et al, 2008;Van Rensburg et al, 2011). The days when the sole purpose of irrigation was to increase crop production are now in the distant past.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation